1994
DOI: 10.1152/ajpheart.1994.267.1.h344
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic neural reactivity to stress does not increase with age in healthy humans

Abstract: Sympathetic nervous system reactivity to stress is though to increase with age in humans. We tested this hypothesis by recording postganglionic sympathetic nerve activity to skeletal muscle (MSNA) (peroneal microneurography) and by measuring plasma norepinephrine concentrations (PNE), heart rate, and arterial pressure before (prestress control) and during cognitive challenge (mental arithmetic and colored word test), thermal stress (i.e., the cold pressor test), and exhaustive isometric handgrip exercise (40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
84
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 0 publications
17
84
5
Order By: Relevance
“…17 A prior report has suggested that attenuated MSNA response to handgrip in the aged is due to higher resting MSNA and not to muscle reflex attenuation per se. 18 Our study also demonstrates higher resting MSNA in older subjects. 18 However, we have shown that progressive ischemia used to progressively and systematically engage the muscle reflex led to multiple attenuated indices of MSNA ( Figure 1D through 1G) as well as BP in the aged ( Figure 1A).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…17 A prior report has suggested that attenuated MSNA response to handgrip in the aged is due to higher resting MSNA and not to muscle reflex attenuation per se. 18 Our study also demonstrates higher resting MSNA in older subjects. 18 However, we have shown that progressive ischemia used to progressively and systematically engage the muscle reflex led to multiple attenuated indices of MSNA ( Figure 1D through 1G) as well as BP in the aged ( Figure 1A).…”
Section: Discussionsupporting
confidence: 71%
“…18 Our study also demonstrates higher resting MSNA in older subjects. 18 However, we have shown that progressive ischemia used to progressively and systematically engage the muscle reflex led to multiple attenuated indices of MSNA ( Figure 1D through 1G) as well as BP in the aged ( Figure 1A). The fact that both BP and MSNA were attenuated and the fact that data in Figure 1 were compared with E1 and not baseline leads us to believe that differences in resting MSNA between young and old subjects cannot totally explain our findings.…”
Section: Discussionsupporting
confidence: 71%
“…Studies of adults exercising in cold environments are few and generally limited to those using varied methodology exploring either the control of cutaneous blood flow during exercise (46) or the performancerelated effects of cold acclimation (17,57,61). At thermoneutral temperatures, older adults exhibit either similar (21,40,49) or blunted (26,33,48) increases in MSNA and BP during static HG compared with the increases demonstrated in young adults. Consistent with these previous studies, we report no agerelated differences in the sympathetic and pressor responses to static HG at baseline (i.e., mean T sk 34.0°C).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be mediated via impairments in the sympathetic control of the cardiovascular system and BP regulation during combined cold stress and isometric exercise. At thermoneutral temperatures (ϳ20 -22°C), the increases in MSNA during isometric handgrip (HG) in healthy older adults have been shown to be either similar to (21,40,49) or less than (26, 33, 48) the increases observed in young adults. Studies of both young and older subjects exercising in cold environments are surprisingly limited.…”
mentioning
confidence: 99%
“…1 Moreover, reduced sympathetic nervous system activity, augmented sympathetic inhibition, and higher cardiac vagal tone in women, compared with men, have all been described. [1][2][3][4][5] Finally, the responsiveness to stressor stimuli may be diminished in women compared with men as well. 1 In summary, despite the overall increase in sympathetic activity with aging, for any given age women seem to have less sympathetic drive than men.…”
mentioning
confidence: 99%